PERKEMBANGAN PSIKOSOSIAL PADA MASA KANAK PERTENGAHAN - Hilya, Aufa Rahma (FAKULTAS ILMU TARBIYAH DAN KEGURUAN UNIVERSITAS SAINS AL-QUR'AN, 2023)
This study reviews psychosocial development in middle childhood. Then, this journal aims to understand about self-esteem, self-development, emotional growth, child in family, family atmosphere, family structure, relationship with siblings, children in peer groups, mental health in middle childhood. As for this type of research, it uses library studies and research uses various methods to gather data, such as literature searches, book lists, journal lists and searches from the Internet. Middle childhood consists of six years of age to the time when a person becomes an adult. The entry of a child into the first grade of elementary school marks the beginning of the Middle Ages. Entry into first grade is an important event for most children that changes their attitudes, values, and behavior.